Random access quantum information processors using multimode circuit quantum electrodynamics - R. K. Naik (Nature Portfolio, 2017)
Despite their versatility, superconducting qubits such as transmons still have limited coherence times compared to resonators. Here, the authors show how to use a single transmon to implement universal one-qubit and two-qubit operations among nine qubits encoded in superconducting resonators’ eigenmodes.